-4
Math is your friend.
2006-09-10 21:46:39
·
answer #1
·
answered by Ian 3
·
0⤊
1⤋
First you need to get all terms with a variable on one side (usually we use the left side for the variable, but it doesn't have to be that way), and all terms without a variable on the other side. To get 2x to "move" to the left side, we have to perform the opposite operation...like right now, its positive, which is the same as adding it to zero, so we want to subtract it. Whatever you do to one side (of the equal sign) you HAVE to do to the other, so if we subtract 2x from the right, we have to subtract it from the left.
3x + 4 - 2x = 2x - 2x
Then we combine like terms on each side of the equal sign by looking at the coefficients of the terms that have the same variable. 3x and -2x can be combined on the left (think: 3 - 2) and 2x and -2x can be combined on the right (think: 2 -2). So...
3x-2x=1x and 2x-2x=0, which means your equation becomes:
1x + 4 = 0.
To get the number on the right, do the same thing, but subtract 4 from both sides....1x + 4 -4 = 0 - 4 and by combining like terms,
1x = -4
(Remember if the coefficient of a monomial term is 1, you don't have to write it, so your answer could be written: x = -4)
2006-09-10 19:51:30
·
answer #2
·
answered by Kate T 1
·
0⤊
1⤋
3x + 4 = 2x
3x + 4 - 2x = 2x - 2x
x + 4 = 0
Collecting like terms
x + 4 - 4 = - 4
Subtracting - 4 from both sides of the equation
x = - 4
The answer is x = - 4
2006-09-10 20:13:06
·
answer #3
·
answered by SAMUEL D 7
·
0⤊
1⤋
x = -4
2006-09-10 19:46:35
·
answer #4
·
answered by iheartcoachard 2
·
0⤊
1⤋
x=-4
2006-09-10 19:58:24
·
answer #5
·
answered by Amar Soni 7
·
0⤊
1⤋
3x-2x+4=0
then x+4=0
soooo x=-4......
2006-09-10 19:45:27
·
answer #6
·
answered by applejacks 3
·
0⤊
1⤋
3x+4=2x
3x-2x= - 4
x= - 4
2006-09-10 19:46:08
·
answer #7
·
answered by loretta 4
·
0⤊
1⤋
-4
2006-09-10 19:44:56
·
answer #8
·
answered by FlashGordon 3
·
0⤊
0⤋
3x + 4 = 2x
-3x -3x (subtract 3x from each side)
4 = -1x (divide each side by negative 1)
/-1 /-1
-4 = x
2006-09-10 19:45:54
·
answer #9
·
answered by Shay 1
·
0⤊
1⤋
Subtract 4 from both sides. Subtract 2x from both sides. The result is
3x - 2x = -4
Now combine terms and you have your answer.
2006-09-10 20:02:31
·
answer #10
·
answered by alnitaka 4
·
0⤊
1⤋
subtract 3x from both sides to arrive at 4=-1x
divide -1x into both sides
x=-4
2006-09-10 19:57:17
·
answer #11
·
answered by Simplystunning 4
·
0⤊
1⤋